Renillenoic acids: Feeding deterrence and antifouling properties of conjugated fatty acids in Patagonian sea pen - García Matucheski, Stella (2012)
Chemical studies in the octocoral Renilla octodentata from San Jorge Gulf (Patagonia, Argentina) have been carried out for the first time. Two conjugated polyunsaturated fatty acids, 1 and 2, named renillenoic acids (RAs), were isolated and characterized from the sea pen. These compounds, analogs of eicosapentaenoic acid (EPA) and arachidonic acid (AA), accounted for a large fraction (20%) of the organic extract of the octocoral. Renillenoic acids were uniform distributed in rachis and peduncle and showed comparable volumetric concentrations, 1.61±0.51 mg/cm3 and 2.00±1.01 mg/cm3 respectively (Paired Student´s t-test, two tailed,p>0.05). Below physiological concentrations, octocoral extracts (28.20 mg/g), rachis tissue and sclerites (0.66±0.02 g/g) showed feeding deterrence against the generalist fish Pagrus pagrus (Fisher exact test, one tailed, pb0.0443). Antifouling assays using larvae of the crustacean Amphibalanus amphitrite revealed antisettlement activity of octocoral extracts (acetone extract=1.49 mg/L, diethyl ether extract=3.16 mg/L). Renillenoic acids 1 and 2 were active against cypris larvae (EC50=4.09 mg/L) and showed favorably low toxicities against nauplii and cyprids (LC50 over 100 mg/L). The results suggest that chemical and physical defense of R. octodentata operate additively or synergistically to protect the sessile organisms from generalist predators and biofoulers.